Spice-derived phenolic, malabaricone B induces mitochondrial damage in lung cancer cells via a p53-independent pathway. Issue 11 (15th October 2018) - Tyagi, Mrityunjay; Maity, Biswanath; Saha, Bhaskar; Bauri, Ajay Kumar; Subramanian, Mahesh; Chattopadhyay, Subrata; Patro, Birija Sankar
Abstract : The spice-derived phenolic, malabaricone B induces mitochondrial cell death and reduces lung tumor growth in vivo . Abstract : The spice-derived phenolic, malabaricone B (mal B) showed selective toxicity to human lung cancer (A549), malignant melanoma (A375) and T cell leukemia (Jurkat) cell lines, without showing toxicity to human normal intestinal (INT407), human kidney (HEK293) and lung fibroblast (WI-38) cells. Among the chosen cancer cell lines, mal B showed maximum cytotoxicity to the A549 cells (IC50 = 8.1 ± 1.0 μM), which was significantly better than that of curcumin (IC50 = 26.7 ± 3.1 μM). Further morphological studies by phase contrast microscopy and a clonogenic assay of the A549 cells revealed that mal B treatment increased the number of shrinking cells and also abolished the clonal proliferation of the cells. Mal B induced apoptotic cell death was confirmed by DNA laddering and quantified by cytoplasmic oligonucleosome formation and annexin V/PI assays. The mal B-induced apoptosis was mediated by an increase in the intracellular reactive oxygen species (ROS), because the cell-permeable antioxidants, N -acetylcysteine (NAC) and PEG-SOD, strongly inhibited its cytotoxicity to the A549 cells. Mal B increased the BAX level while simultaneously decreasing the BCL-2 and BCL-XL levels in the A549 cells, triggering the mitochondrial apoptotic pathway as revealed from the release of cytochrome c, and the activation of caspase-9 and caspase-3. Pre-treatment of cells with caspase-9, caspase-3 and pan-caspase inhibitors made them more resistant to mal B treatment. This effect of mal B was strongly associated with the concomitant decrease in anti-apoptotic (IAP1, IAP2 and survivin), angiogenic (growth factors) and cancer invasiveness (matrix metalloproteinase-9, COX-2) modulating proteins. Mal B induced cytotoxicity was unaffected by the shRNA-mediated depletion of p53 in A549 cells. Most importantly, mal B sensitized a wide range of human carcinoma cells regardless of their p53 status. Finally, mal B (100 mg kg −1 ) also inhibited lung tumor (xenograft) growth in SCID mice.